(untitled) (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: Previously, we have shown that predicted zymogen granule protein 16 homolog B (P-G3MZ19) existed in Bali cattle (Bos javanicus) saliva. It was suggested that P-G3MZ19 is a member of the mannose-binding lectin family that plays an essential role in innate immunity. In the present study, we aimed to analyze the structure and ligand-binding of P-3MZ19 in Bali cattle saliva. Materials and Methods: Saliva of four adult healthy Bali cattle was collected, lyophilized, and subjected to two-dimensional (2-D) gel electrophoresis. The target spot of around 17 kDa related to P-G3MZ19 was excised for matrix-assisted laser desorption ionization time-of-flight mass spectrometer/time-of-flight mass spectrometer mass spectrometry analysis and sequencing. The structure and the ligand-binding of P-3MZ19 were analyzed using bioinformatics software programs published elsewhere. Results: Based on Iterative Threading ASSEmbly Refinement the 3D model of P-G3MZ19 was suggested to have similarities to exo-alpha-sialidase (EC 3.2.1.18); while its ligand-binding sites consisted of seven residues, i.e., 25aa-26aa (Gly-Gly), 95aa (Phe), 138aa (Tyr), 140aa (Leu), 141aa (Gly), and 143aa (Thr). Conclusion: The structure of P-G3MZ19 of Bali cattle saliva and its ligand-binding sites have been successfully determined by using bioinformatics techniques. The biological and immunological roles of the peptide are currently under investigation based on P-G3MZ19 synthetic peptides. J. Adv. Vet. Anim. Res., 8(2): 224-229, June 2021